2018
DOI: 10.1332/030557317x15120417452025
|View full text |Cite
|
Sign up to set email alerts
|

Street-level practice and the co-production of third sector-led employability services

Abstract: Policymakers have promised a personalised approach to improving the employability of disadvantaged groups. The evidence suggests that contracted-out activation programmes in the UK and some other welfare states have instead sometimes delivered a standardised 'work-first' model. An alternative approach is exemplified in local employability services targeting lone parents in Scotland, led by third sector–public sector partnerships. Our research on these services suggests a link between programme governance (defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…The fact that local third sector organisations were granted the resources and had the expertise to contribute was also important. It has been suggested that the third sector has a particular capacity to co-produce with vulnerable user groups and communities (Pestoff, 2012), and our evidence suggests that this was the case with MIW (Lindsay et al, 2018a).…”
Section: Miw Service User North Lanarkshire 2014supporting
confidence: 53%
See 1 more Smart Citation
“…The fact that local third sector organisations were granted the resources and had the expertise to contribute was also important. It has been suggested that the third sector has a particular capacity to co-produce with vulnerable user groups and communities (Pestoff, 2012), and our evidence suggests that this was the case with MIW (Lindsay et al, 2018a).…”
Section: Miw Service User North Lanarkshire 2014supporting
confidence: 53%
“…There are few opportunities for users to exercise agency or shape the content of services. While the government and its contracted providers use the language of partnership, many third sector organisations and other expert agencies have found themselves denied funding and excluded from service delivery (Lindsay et al, 2018a). As a result, there is little evidence of co-production or personalisation in how vulnerable jobseekers like LPs experience services.…”
Section: Co-production As a Route To Personalised Employability Servicesmentioning
confidence: 99%
“…Social innovation is impossible where the right to “act, organize or provide differently” is denied (Evers and Ewert, , p. 120). The dominance of NPM governance legacies within the UK public management regime (which, despite political devolution and some distinctive features of a so‐called “Scottish approach” to employability, also infect policy‐making in Scotland) mean that norms around centralized state control and privatized/contractualized service delivery have proved difficult to challenge (Lindsay et al, forthcoming). Policy‐makers sometimes also claim to be unconvinced as to the efficiency and scalability of co‐produced social innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Ewert and Evers's () emphasis on the value of co‐production as a key concept in building more responsive and innovative employability services connects with a growing evidence base on “what works” in street‐level practice to support people with complex needs to escape poverty and/or progress in the labour market (Lindsay et al, forthcoming). Brandsen and Pestoff () and Pestoff () have differentiated between “co‐production” at the frontline, where users produce and shape their own services in collaboration with street‐level workers, and two potential facilitating mechanisms: “co‐governance”, in which different stakeholders participate actively in the design and planning of services on the basis of shared decision‐making and responsibility; and “co‐management”, referring to collaboration across stakeholders in resourcing and delivery, based on the idea that services will be more effective where resources and expertise are pooled among different organizations and stakeholder groups.…”
Section: Social Innovation and Co‐production In Employability Servicesmentioning
confidence: 99%
“…There are clear potential benefits in promoting co‐production in shaping street‐level interactions, and co‐governance and co‐management in service design and management. Co‐production has the potential to deliver the personalization promised but rarely achieved in policy areas such as employability—services designed with users to draw on their assets are more likely to offer genuine opportunities for them to make choices and personalize their own journeys towards employability (Lindsay et al ). Personalized services that are responsive to individuals' needs are likely to increase the buy‐in and commitment of users, address their specific barriers, and thus support them to make progress (Garven et al ).…”
Section: Background To the Researchmentioning
confidence: 99%